2016
DOI: 10.1117/1.jbo.21.9.091314
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory diffuse optical tomography and multimodality physiological monitoring system for muscle and exercise applications

Abstract: Ambulatory diffuse optical tomography (aDOT) is based on near-infrared spectroscopy (NIRS) and enables three-dimensional imaging of regional hemodynamics and oxygen consumption during a person’s normal activities. Although NIRS has been previously used for muscle assessment, it has been notably limited in terms of the number of channels measured, the extent to which subjects can be ambulatory, and/or the ability to simultaneously acquire synchronized auxiliary data such as electromyography (EMG) or electrocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 79 publications
0
28
0
Order By: Relevance
“…34 Because the muscle oxygenation/hemodynamic status of a muscle group is not well represented by a single point measurement within that muscle group, 14 the mean values of a multipoint measurement might be more suitable for representing the muscle oxygenation/hemodynamic status of that muscle group. The temporal resolution (23 Hz) of this NIRS system was high enough for characterizing the general muscle oxygenation/hemodynamic response whose time scale was nearly one second.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34 Because the muscle oxygenation/hemodynamic status of a muscle group is not well represented by a single point measurement within that muscle group, 14 the mean values of a multipoint measurement might be more suitable for representing the muscle oxygenation/hemodynamic status of that muscle group. The temporal resolution (23 Hz) of this NIRS system was high enough for characterizing the general muscle oxygenation/hemodynamic response whose time scale was nearly one second.…”
Section: Discussionmentioning
confidence: 99%
“…10 By utilizing high spatial resolution imaging techniques, such as magnetic resonance spectroscopy (MRS) and positron emission tomography (PET), it can be observed that even in different parts of the same muscle, the oxygen uses varied significantly. 14 Unfortunately, the aforementioned imaging techniques are intrinsically limited by the large size, very high cost, and the strict constraints on the exercise modality. This highlights the importance of spatially resolved measurements, which not only informs basic muscle physiology and potentially helps improve muscle training paradigms, 13 but also supports clinical decision making.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, Kimoto et al proposed a new layered sensor for simultaneous measurements of EMG, mechanomyography (MMG), and CW-NIRS, which was tested during a cuff occlusion [88]. In 2016, Hu et al developed an integrated 64-channel portable CW-NIRS instrument with physiological sensors [89]. These sensors were: High-resolution EMG, electrocardiography (ECG), electrooculography (EOG), and electroencephalography (EEG) sensors.…”
Section: Nirs and Emg Hwmentioning
confidence: 99%
“…A recent review has nicely summarized the role of the EMG-NIRS combination in clinical practice [ 11 ]. Recently, several prototypes integrating EMG and NIRS have been developed [ 12 , 13 , 14 , 15 , 16 ]. However, those devices presented several limitations; in particular, they did not measure regional muscle O 2 Hb saturation (instead they provided only oxygenation changes) and partially used full textile sensors for EMG.…”
Section: Introductionmentioning
confidence: 99%